An assessment of the short-term impact of COVID-19 on economics and the environment: A case study of Indonesia - Marissa Malahayati; Toshihiko Masui; Lukytawati Anggraeni (EconomiA, 2021)
The COVID-19 pandemic has already made a significant impact on various sectors. No country was fully prepared to face this global pandemic, and Indonesia is no exception. For Indonesia, this pandemic shook not only the public health service system but also the economy. This study makes projections related to the impact of this pandemic on the Indonesian economy by utilising a computable general equilibrium (CGE) model. Additionally, we calculate the land needed to cover the demand for agricultural products, as well as the level to which emissions can be reduced. Our simulation shows that, along with every shock caused by COVID-19 to national supply and demand, Indonesia will be experiencing economic stagnation by 2021, with the gross domestic product (GDP) level 4-8% lower than the business as usual (BAU) level during the pandemic (2020-2021). The two sectors that will be hit hardest are the transportation and tourism sectors, making up a GDP loss ranging from 30% to 50%. During this stagnation, the agricultural sector is a potential sector for accommodating workers who have been laid off. The model also predicts that there will be a temporary land-use change that the farmers will prefer to use their land for food and horticultural commodities. As for emissions, our calculations show that the potential for emission reductions will be up to 8% by 2021, compared to the BAU level. However, the source of this emission reduction is not positive as it comes from the restriction of economic activity, and the growth in emissions from the industrial and waste sectors are still increasing rapidly, even during the pandemic. Thus, it is feared that there will be a very high spike in emissions when the pandemic ends, making the situation more challenging for Indonesia to achieve its emission mitigation targets. Furthermore, once the government introduces fiscal incentives to support the economy during the pandemic, the economic condition will be improved, although still not fully recovered. The model predicts that the government fiscal incentives may help to improve the GDP by around 1-3%, compared to when no incentive is introduced.
Keywords: 330; Computable general equilibrium (CGE); COVID-19; Emission reduction; Land demand